Efficacy of Intravenous Vitamin K in Correcting Deranged International Normalized Ratio in Chronic Liver Disease - Muhammad Hussain, Sana; sajjad, Tahreem; Zaidi, Shaheera; Abbasi, Amanullah (Journal of Liaquat University of Medical & Health Sciences, 2026)
OBJECTIVE: To study the efficacy of intravenous vitamin K in deranged INR in chronic liver disease. METHODOLOGY: This observational cross-sectional study at a tertiary care hospital included CLD patients (?18 years) with baseline INR >1.3 who received three doses of vitamin K. Exclusions were acute liver failure, missing INR data, anticoagulant use, or blood transfusion within 72 hours before or between PT-INR sampling. The mean INR change was compared by dosing frequency (single vs multiple) and Child–Pugh class. Data were analyzed using SPSS version 24. RESULTS: 80 patients included, with 58.75% males and 41.25% females, of whom CTP A, B, and C were 5%, 15%, and 80%, respectively. The mean change in INR after the 1st and 3rd doses was 0.078±0.265; P = 0.01 and 0.1403±0.382; P = 0.002, respectively. The mean change in INR between single versus three doses was -0.056±0.33; P = 0.049. The mean change in INR after the 1st and 3rd doses in CTP A was 0.195±0.404; P=0.001 and 0.0250±0.635; P=0.005, respectively. The mean change in INR after the 1st and 3rd doses in CTP B was 0.0825±0.449; P = < 0.001 and 0.0717±0.15; P= < 0.001, respectively. The mean change in INR after the 1st and 3rd doses in CTP C was 0.077±0.299; P= < 0.001 and 0.160 ± 0.420; P= < 0.001, respectively. CONCLUSION: Overall, the majority of CLD patients showed improvement in INR after three doses of vitamin K, primarily CTP C.